Criticism of Sharia Banks in Indonesia (an Analysis of Zaim Saidi's Thoughts) - Zain, Zainur; Kamal, Jaidil; Rahmawati, Indah (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2024)
Zaim Saidi, in his academic argumentation, states that current banking practices are in a state of comfort, resulting in the neglect of several sharia provisions under the argument that they are not yet prepared to implement them because they are still in a transitional period. Subsequently, Zaim Saidi asserted that Islamic banking and conventional banking are not entirely equivalent, but rather only 99.9% so. Islamic institutions may be exempt from the interest system; however, it is nearly impossible to be exempt from the usury system. The research question is as follows: "What is Zaim Saidi's conceptual framework regarding Islamic banking in Indonesia?" This research is a qualitative study that is equivalent to descriptive research methods. It employs data-driven analysis, utilizing existing theories as supporting material, and generating theories. This qualitative research pertains to normative data that is closely associated with bibliographic data. Consequently, this form of research is classified as library research.This investigation identified three critiques of Islamic banking by Zaim Saidi: fiat money is usury, the application of the wadi'ah and mudharabah contracts in deposits at Islamic banks is flawed, and murabahah is an illegal transaction. Zaim Saidi's foundational reasoning in Islamic jurisprudence is predicated on the perspectives of classical scholars who articulate their arguments in a more textual manner. In this instance, the bank's intermediation function is undermined, and significant costs are incurred because of the conflict between international regulations and the implementation of Zaim Saidi's concepts in Islamic banking in Indonesia.